STUDY ON THE IMPORTANCE OF USING AGRIVOLTAIC SYSTEMS TO REDUCE THE EFFECTS OF CLIMATE CHANGE - Liviu MARCUTA; Cristiana TINDECHE; Alina Cristina NUTA; Florian Marcel NUTA; Alina MARCUTA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Climate change, global warming are phenomena that have changed the face of the world and that have a direct impact on agricultural production and food security, given that the world's population is growing from one year to the next, without the possibility of growth and natural resources. Another worrying phenomenon is the production of greenhouse gases and their destructive effect on the planet. That's why the technology that is being perfected every day tries to find solutions that simplify both the efforts made to obtain food, but also the possibility of increasing the efficiency of production processes. In this way, in the agricultural field, the idea of developing dual systems appeared, which would protect both agricultural crops, with the aim of increasing productivity, but which would also contribute to obtaining solar energy, necessary not only for own consumption, but also to be included in consumer networks, the proposed concept being that of the AgriVoltaic system. The idea that appeared in 1981 began to be developed, currently reaching the development of a technology that is starting to be adopted in many countries of the world, including Romania. In the current paper, we propose to analyze the opportunity of using AgriVoltaic technology, its advantages and disadvantages, but also the way in which it could contribute to increasing the profitability of agricultural farms. At the same time, increasing the degree of awareness regarding the advantages of introducing agricultural systems and the method of implementing the systems is another objective of the current work. Starting from the analysis of the specialized literature, we outlined the term Agrivoltaic technology and continued the study with an analysis of the possibilities of implementing this technology in Romania, due to the solar energy potential that it benefits from. The research methodology assumed on the one hand the bibliographic analysis, and on the other hand the analysis of the development potential of the system, taking into account the existing agricultural areas and crops suitable for this system. As a result of the research carried out, it turned out that although there are confirmed advantages of using AgriVoltaic technology, it does not yet benefit from sufficient visibility or high accessibility among farmers. Also, the existing legislation at the level of Romania does not yet make possible the development of the dual system. Among the disadvantages of using agrivoltaic systems are the still high costs, but the measures to protect the rural landscape, which occupies an important place in sustainable development, even if the energy produced is renewable.